2008
DOI: 10.1007/s11671-008-9204-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Iron Oxide Magnetic Nanoparticles on Smooth Muscle Cells

Abstract: Recently, magnetic nanoparticles of iron oxide (Fe3O4, γ-Fe2O3) have shown an increasing number of applications in the field of biomedicine, but some questions have been raised about the potential impact of these nanoparticles on the environment and human health. In this work, the three types of magnetic nanoparticles (DMSA-Fe2O3, APTS-Fe2O3, and GLU-Fe2O3) with the same crystal structure, magnetic properties, and size distribution was designed, prepared, and characterized by transmission electronic microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 35 publications
2
38
1
Order By: Relevance
“…It is a biodegradable and feasible agent for study of living cells by MRI in vitro and in vivo. 14,23 Due to the phagocytic properties and negative membrane potential of dendritic cells, SPIO-labeled nanoparticles could be easily delivered to the cells. 24 In our study, SPIO was internalized into dendritic cells, and this was confirmed by Prussian blue staining (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…It is a biodegradable and feasible agent for study of living cells by MRI in vitro and in vivo. 14,23 Due to the phagocytic properties and negative membrane potential of dendritic cells, SPIO-labeled nanoparticles could be easily delivered to the cells. 24 In our study, SPIO was internalized into dendritic cells, and this was confirmed by Prussian blue staining (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…As an n-type semiconductor with a small band gap (2.1 eV), ␣-Fe 2 O 3 is a highly stable and relatively low-cost material widely used for field emission (Hsu, Li, & Hsiao, 2008), biomedicine (Zhang et al, 2009), water splitting (Kevin, Florian, & Michael, 2009), photooxidation (Mohapatra, John, Banerjee, & Misra, 2009), lithiumion battery (NuLi, Zeng, Zhang, Guo, & Liu, 2008), pigmentation (Legodi & de Waal, 2007), catalysis (Zheng et al, 2006), gas sensing (Chen, Xu, Li, & Gou, 2005), purification (Zhang et al, 2005), and solar energy conversion (Ohmori, Takahashi, Mametsuka, & Suziki, 2000). Recently, many efforts have been spent in the synthesis of a variety of novel one-dimensional (1D) and three-dimensional (3D) ␣-Fe 2 O 3 structures for chemical and physical studies and potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, carboxyl-functionalized poly(amidoamine) (PAMAM) dendrimer-stabilized iron oxide nanoparticles have been shown to be taken up into human epithelial carcinoma cells presumably either through pinocytosis or via direct diffusion through the cell membrane [31]. The cellular uptake of DMSA@MNPs in different cell lines was found in many studies including our study in which smooth muscle cells were employed [32]. The internalization of negatively charged nanoparticles may occur through nonspecific binding and clustering of the particles on the scarce cationic sites on the plasma membrane and their subsequent endocytosis.…”
Section: Cellular Uptake and Processingmentioning
confidence: 55%
“…More recently, much effort has been devoted to investigating the cytotoxicity of MNPs or just confirming the biocompatibility of synthesized MNPs with different surface coatings. Different surface-modified MNPs, including those coated by dextran [43][44][45], heparin [46], DMSA [29,32], APTS [32], GLU [32], protamine [47], lipid [44,45], PEG and their derivatives [33], silica [12], as well as bare MNPs [48], were evaluated. A series of targeting cell lines were used in vitro for testing including phagocytic [49], neural [48], hepatic [47], epithelial [49], stem and progenitor cells [50], immune and blood cells [49,51] and various cancer cell lines [48].…”
Section: Cytotoxicity Evaluationmentioning
confidence: 99%